TRADISI SEDEKAH BUMI DI DESA KUNDURAN - Mustika Faradilla Shanti (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Culture and society are two things that cannot be separated, both are closely related and go hand in hand. Sedekah bumi is one of the cultural agrarian societies that continues to be maintained from time to time, including the culture of sedekah bumi carried out by the people of Pancur Temayang village in Kundeuran . Sedekah bumi tradition has become a routine part of the routine carried out every year by the Pancur community as a form of appreciation for God who has bestowed His fortune through abundant crops so that people can fulfill their daily needs. In conducting this research, researchers used a qualitative method with an ethnographic approach as a basis for conducting observations in the field because researchers needed to enter directly into the object of research to explore the meaning and value of tradition understood by the Pancur village community in carrying out the sedekah bumi tradition. Explained that sedekah bumi carried out by the people of Pancur village has several value benefits, including sociological values, namely with the existence of these activities, the social ties of people from various groups unite. Theological value, namely the implementation of the sedekah bumi as an expression of gratitude for maintaining good relations with God. Ecological value, the existence of sedekah bumi carried out in the village spring, give confidence to the community that the existence of the village spring must be preserved, and the existence of the surrounding ecosystem must also be maintained. In addition, sedekah bumi tradition also received a variety of responses from the village community, some agreed and some did not agree with the implementation of this tradition.